Analisis Penambahan Methanol 5%, 10% dan 15% Terhadap Torsi, Daya dan Exhaust Gas Temperature (EGT) Mesin Bensin 150 CC Berbahan Bakar Pertamax - Fatkhurrozak, Faqih; Lukman Sanjaya, Firman; Syarifudin; Nur Akhmadi, Amin; Ariyanto, Nur Aidi; Gunawan (P3M Politeknik Negeri Cilacap, 2024)
Indonesia is one of the countries that uses the most motorized vehicles, which increases air pollution and fuel crises. Using biofuel is one solution to overcome this problem. Methanol is used as a mixture of Pertamax to produce environmentally friendly and renewable biofuel. This is because methanol has high octane and oxygen. Mixing methanol in Pertamax was carried out to analyze the impact of Torque, Power, and Exhaust Gas Temperature (EGT) of a 150cc petrol engine. Methanol 5%, 10%, and 15% was mixed into Pertamax with engine speed variations of 1000, 2000 and 3000 rpm. Dynotest is used to measure engine performance and thermocouples to measure EGT. Test results show the highest increase in engine torque and power of up to 25% at a speed of 2000 rpm with the PM15 mixture compared to P100. The highest reduction in EGT value occurred when using the PM15 mixture at a speed of 1000 rpm up to 28% compared to P100. This shows that the addition of methanol to Pertamax increases torque and power and reduces the EGT of the gasoline engine.